Apoptosis of Platelets Inhibited By Herba Sarcandrae Extract through the Mitochondria Pathway. (18th November 2018) - Zhu, Xiaoqin; Jiang, Yiling; Zheng, Qin; Zhang, Aiping; Shi, Ling; Xia, Lemin; Luo, Meihong
Abstract : The purpose of the present study is to decode the underlying mechanism of Herba Sarcandrae that indicated antipurpuric effect and to unveil one of its primary components, flavonoids, which play an important role. An immune mediated bone marrow failure (BMF) model in mouse was established by infusion thymus suspension cells after radiation in vivo. Platelets isolated in vitro were prepared from normal mice and BMF mice, respectively. The expressions of PS, P-selectin, PAC-1, Bax, Bad, Bid, and caspase-9 were examined by flow cytometry, and alteration of morphology of platelets under different conditions was observed. Our results indicated that the number of platelets was increased by addition of total flavonoids, and some of apoptotic markers such as Bax, Bad, Bid, and Caspase-9 were downregulated. In addition, the phosphatidylserine (PS) exposure on platelets was inhibited by total flavonoids, and the expressions of PAC-1 and P-selectin were decreased. In conclusion, it is suggested that the total flavonoids of Herba Sarcandrae may inhibit the excessive platelet apoptosis through mitochondrial pathway. In addition, activation of platelets may be also involved in mediating apoptosis of platelets.